مقارنة أداء آلة تبريد امتصاصية باستخدام المحاليل الثنائية (ماء / بروميد الليثيوم وأمونيا / نترات الليثيوم) - زيود, رامي (Latakia University Journal -Engineering Sciences Series, 2019)
يتناول البحث إجراء مقارنة لأداء آلة تبريد امتصاصية أحادية المرحلة باستخدام المحاليل الثنائية (ماء / بروميد الليثيوم وأمونيا / نترات الليثيوم) عند شروط حرارية مختلفة لكل من المولد والمبخر والمكثف من خلال النمذجة والمحاكاة باستخدام برنامج حاسوبي EES. بينت النتائج أن دارة (أمونيا – نترات الليثيوم) يمكن أن تستخدم للتكييف وتعطي أداء أفضل من دارة (ماء / بروميد الليثيوم) عند درجات حرارة المولد المنخفضة, وبالتالي إمكانية تشغيلها باستخدام الطاقة الشمسية الحرارية. يزداد معامل الأداء لكل دارة مع ازدياد كل من درجة حرارة المولد والمبخر. يسبب ازدياد درجة حرارة المكثف انخفاضاً في أداء النظام لجميع الدارات. تساعد هذه النتائج في اختيار ظروف التشغيل للنظم القائمة وتحقيق التشغيل الأمثل لها. This study discusses comparative the efficiency of single stage absorption refrigeration machine using binary solutions (water/lithium bromide, ammonia/ lithium nitrate) at various generator, evaporator, and condenser temperatures through modeling and simulation using EES program. The results show that the lithium nitrate – ammonia may be used for conditioning which gives better performance than the water- lithium bromide cycle at low generator temperature, thus the possibility of operation using the solar thermal energy so may be work by solar thermal energy. Increasing generator temperatures and evaporator cause a increasing in system performance. Increasing condenser temperatures cause a decrease in system performance for each cycle. These results can be used in selecting operating conditions for existing systems and for maintain optimum operation of the system.